Safety and efficacy of fingolimod in Iranian patients with relapsing-remitting multiple sclerosis: An open-label study - Rozita Doosti; Abdorreza Naser Moghadasi; Amir Reza Azimi; Shahrokh Karbalai Saleh; Masoud Etemadifar; Vahid Shaygannejad; Fereshteh Ashtari; Mohammad Hossein Harirchian; Bahaadin Siroos; Hormoz Ayramloo; Nastaran Majdinasab; Seyyed Mohammad Masood Hojjati; et al. (Babol University of Medical Sciences, 2021)
Background: Fingolimod was the first oral therapy approved for treating relapsing-remitting multiple sclerosis (RRMS) in 2010. This open-label study evaluated the safety and efficacy of fingolideR, 0.5 mg in Iranian MS patients during one-year follow-up. Methods: A multicenter, open-label, longitudinal was designed to evaluate the safety and efficacy of fingolideR, 0.5 mg over a one-year follow-up period across 11 centers. The patients were visited by their neurologists every two months to evaluate possible adverse events and clinical disease activity considered by recording Kurtzke's Expanded Disability Status Scale (EDSS). Results: A total of 252 patients with the mean treatment duration of 343±45.70 days were. 20 patients experienced adverse events (AEs) and serious adverse events (SAEs) such as resistant urinary tract infection (UTI), premature atrial contraction (PAC), skin allergic reaction, macular edema, chicken pox, zona, panic attacks, and exacerbations associated with steroids treatment, all of which led to FingolideR discontinuation. The mean EDSS decreased from (2.15±1.29, 95%CI: 1.99to2.32) at baseline to (1.85±1.22, 95%CI: 1.68to2.02) at 12th month (final visit) while a p-value revealed significant differences comparing baseline and final EDSS (p<0.001). Mean annualized relapse rate (ARR) of the patients in one year prior to the study was (0.006±0.016, 95%CI: 0.004to0.008) which changed to (0.005±0.016, 95%CI: 0.003to0.007) at the end of the study period. Patients with a 12-month period of fingolideR treatment experienced sustained ARR and disease progression (p<0.001). Conclusion: The obtained findings suggest that the administration of FingolideR, 0.5 mg (Fingolimod, Osvahpharma, Tehran, Iran) is safe and efficient for Iranian MS patients.